2008
DOI: 10.1097/01.hmr.0000304489.65028.75
|View full text |Cite
|
Sign up to set email alerts
|

Family medicine practice performance and knowledge management

Abstract: Differences in KM occur within family practices and between family practices and other organizations and may have implications for improving practice performance. Understanding interaction patterns of work relationships and KM may explain why costly technical or externally imposed "one size fits all" practice organizational interventions have had mixed results and limited sustainability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 20 publications
1
34
0
1
Order By: Relevance
“…Existing literature identifies practice organizational characteristics (3940) that may inform these processes, such as the nature of relationships among practice members(41–42), a practice’s ability to work as a team(43), and how a practice manages knowledge (44). Thus, regardless of the model to be used for change, consideration needs to be given to development of a practice’s organizational systems to innovate and deliver high quality care (45), whether chronic disease management or health promotion advice and services.…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature identifies practice organizational characteristics (3940) that may inform these processes, such as the nature of relationships among practice members(41–42), a practice’s ability to work as a team(43), and how a practice manages knowledge (44). Thus, regardless of the model to be used for change, consideration needs to be given to development of a practice’s organizational systems to innovate and deliver high quality care (45), whether chronic disease management or health promotion advice and services.…”
Section: Discussionmentioning
confidence: 99%
“…Our research in family medicine practices has developed a preliminary social-technical model of KM (Orzano, McInerney, Tallia, Scharf, & Crabtree, 2008a, 2008bOrzano et al, 2007c), developed preliminary qualitative and quantitative methods to assess KM and associated organizational attributes (Ohman-Strickland et al, 2007;Orzano et al, 2008aOrzano et al, , 2008bOrzano, Tallia, Nutting, Scott-Cawiezell, & Crabtree, 2006), and suggested that certain KM processes may be associated with improved diabetes outcomes (Orzano et al, 2007b).…”
mentioning
confidence: 99%
“…Therefore, KM is a process that can potentially increase the capacity of a practice to deliver effective care by sharing and making existing explicit and tacit knowledge available among practice members or by developing new knowledge for use by the practice (Orzano, McInerney, Tallia, Scharf, & Crabtree, 2008b). In the vernacular, it is about how one gets members of a practice and patients to ''talk'' about things of mutual interest and benefit.…”
mentioning
confidence: 99%
“…In the vernacular, it is about how one gets members of a practice and patients to ''talk'' about things of mutual interest and benefit. The talk or tool can be as sophisticated as an EMR or as simple as space around the coffee machine for spontaneous conversation (Orzano et al, 2008b). KM appears to affect performance (productivity and workplace satisfaction) and certain traditional disease outcome measures (e.g., blood pressure and blood glucose) by influencing work relationships to enhance learning, decision making, and task execution (Orzano et al, 2008a(Orzano et al, , 2008b.…”
mentioning
confidence: 99%
See 1 more Smart Citation